Faking Christmas - Winfrey, Kerry (Berkley Romance, 2023)
"Laurel Grant works as the social media manager for Buckeye State of Mind, an Ohio tourism magazine and website. She is most definitely not an owner of a farm--specifically, the owner of her twin sister Holly's farm just outside of Columbus--but she lets her boss think she is. Laurel only handles the social media for the farm, but she's happy to keep her little white lie going. And keep it going she must, when Gilbert--recently dumped by his wife--invites himself over for the farm's big holiday dinner (as advertised on Meadow Rise Farm's Instagram, thanks to Laurel herself). Laurel immediately goes into panic mode to figure out how she can trick Gilbert into thinking she's basically the Martha Stewart of rural Ohio and keep her job in the process. Laurel and Holly come up with a plan: all Laurel has to do is pretend to own the farm for one dinner. But when Laurel shows up at the farm, an unwelcome guest is there: Max Beckett, her nemesis since Holly's wedding. The annoyingly attractive man she hates will be posing as Laurel's husband just for the evening, but when a snowstorm traps them all for the entire weekend, Laurel is going to have to figure out how to survive with her job and dignity intact. Whatever the case, this promises to be the most eventful Christmas in ages."--